Recent advance on structural design of high-performance Pt-based nanocatalysts for oxygen reduction reaction - Fu-Rong Yang; Lei Gao; Wen-Chuan Lai; Hong-Wen Huang (Advanced Sensor and Energy Materials, 2023)
Proton exchange membrane fuel cells (PEMFCs) represent a promising technology to overcome the current energy and environmental issues, where high-performance cathodic catalysts are badly needed due to the sluggish kinetics of oxygen reduction reaction (ORR). By far Pt stands for the best ORR catalyst, however, considering the scarcity and high cost, it is imperative to further improve its catalytic activity and atomic efficiency to reduce the loading amount. In view of the key issues, this review concentrates on recent advances on developing high-performance Pt-based nanocatalysts for ORR. The catalytic ORR mechanism was first described, followed by presenting the major principles to regulate ORR activity involving ligand effect and geometric effect. Guided by the principles, typical design strategies of Pt-based nanocatalysts were detailedly summarized, with emphasis on increasing intrinsic activity of single active site and electrochemical active surface area. We finally concluded by providing the remaining challenges and future directions in this field.